A Novel Endogenous Human CaMKII Inhibitory Protein Suppresses Tumor Growth by Inducing Cell Cycle Arrest via p27 Stabilization - Wang, Chunmei (American Society for Biochemistry and Molecular Biology, 2008)
Calcium/calmodulin-dependent protein kinase II (CaMKII) regulates numerous physiological functions. Inhibition of CaMKII activity, mostly by synthetic reagents, has been proved to suppress cell growth in many cases. So far there are no reports about the physiological functions and underlying mechanisms of endogenous CaMKII inhibitory proteins in cell cycle progression. Here we report the characterization of a novel human endogenous CaMKII inhibitor, human CaMKII inhibitory protein α (hCaMKIINα), which directly interacts with activated CaMKII and effectively inhibits CaMKII activity. hCaMKIINα expression is negatively correlated with the severity of human colon adenocarcinoma. Overexpression of hCaMKIINα inhibits colon adenocarcinoma growth in vitro and in vivo by arresting the cell cycle at the S phase through its conserved inhibitory region (27CIR), whereas silencing the hCaMKIINα expression accelerates tumor growth and cell cycle progression. We found that the effect of hCaMKIINα on cell cycle is correlated with up-regulation of p27 expression, which may be due to the inhibition of proteasome degradation, but not transcriptional regulation, of p27. Moreover, hCaMKIINα deactivated MEK/ERK, which is prerequisite to the inhibition of Thr-187 phosphorylation and subsequent proteasomal degradation of p27, causing the inhibition of S-phase progression of cell cycle. The findings underscore a link between hCaMKIINα-mediated inhibition of CaMKII activity and p27-dependent pathways in controlling tumor cell growth and cell cycle and imply a potential application of hCaMKIINα in the therapeutics of colon cancers.